Efforts to Improve Learning Outcomes passing Down Volleyball Variations Through Learning and Modified Ball On Private Junior High School eighth grade students Perbaungan Satria Dharma School Year 2019/2020: Efforts to Improve Learning Outcomes passing Down Volleyball Variations Through Learning and Modified Ball On Private Junior High School eighth grade students Perbaungan Satria Dharma School Year 2019/2020 - Benny Aprial M; Ika Endah Puspita Sari (Institute Of Computer Science (IOCS), 2020)
Research conducted intend to find information about the implementation of learning do bawahd natural passing game of volleyball through the application of learning variations and modifications media delivered with the treatment of class action, namely the existence of the stages in the learning cycle. Volleyball is a sport game that has many fans. To be able to play volleyball it is necessary mastery of basic techniques which include passing, serve, smash, and block. Technique is a way of doing or carrying out something to achieve certain goals efficiently and effectively. Techniques in volleyball games can be interpreted as a way to play the ball efficiently and effectively in accordance with the norm of the game that apply to achieve optimal suatuhasil. Playing field shall be rectangular with a size of 18 meters long and 9 meters wide. The boundary line marked using paint / chalk, of a width not more than 5 cm. After the second cycle of learning to walk and to finish, the student's ability to perform under increased passing. Of the 17 students, there were 15 students have achieved mastery learning value (complete) with an average value of 85.40 and 88.24% percentage of classical completeness. However masihada 2 students who have not gained mastery learning although the value that was obtained has increased in comparison with the passing of learning under volleyball before in terapkannya variety of learning with modifications ball. This is because the student is not able to do most of the prefix attitude indicator, and attitude exercising their end.